Morphometric Malformations in Fetal Rats Following Treatment with Aqueous Leaf Extract of Carica Papaya - Ekong, Moses B; Akpan, Mandu U; Ekanem, Theresa B; Akpaso, Mfon I (Asian Journal of Medical Sciences, 2011)
Objective: Carica papaya popularly known as papaya or pawpaw is a fruit with diverse nutritional and medicinal properties. The continuous use of the leaf extract as enema by pregnant women necessitated this study on the effect of aqueous extract of the young leaves on the morphometry of the fetuses of pregnant Wistar rats. Material & Methods: Twenty seven sexually matured Wistar rats consisting of eighteen females and nine males, and weighing 180-200g were used for the study. The female rats were assigned equally into three groups of A, B and C. Pregnancies were obtained after the introduction of the males into the female cages overnight. On day 12 of preg-nancy, group A (control) was given sham treatment of tap water, while groups B and C were treated with 60mg/kg and 120mg/kg respectively, of the aqueous leaf extract of C. papaya for seven days (days 12-18 of pregnancy). On day 20 of gestation, the animals were anaesthetized using chloroform and euthanized, and the uteri dissected out to study the fetuses. Results: Results revealed reduced number of viable fetuses, reduced fetal weight, and reduced crown-rump, head, and tail lengths in the group treated with 60mg/kg aqueous leaf extract of C. papaya, while there was resorption of all the fetuses in the group treated with 120mg/kg of the aqueous leaf extract of C. papaya. Conclusion: In conclusion, the aqueous leaf extract of C. papaya at the given dosage in this study is detrimental to developing fetuses, and these effects were dose dependent. Hence, the use of the extract especially during the period of gestation should be discouraged. Key Words: C. papaya; fetus; morphometry; malformation; rats DOI: 10.3126/ajms.v2i1.4028 Asian Journal of Medical Sciences 2 (2011) 18-22